Hubungan Pengetahuan, Sikap dan Perilaku Ibu dalam Pemberian Imunisasi Hepatitis B 0-7 Hari di Kota Banjarmasin - Ahmad Rizani, Mohammad Hakimi, Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2009)
Background:  Indonesia  belongs  to medium and  high  endemic country of  hepatitis B  (HB) with  the prevalence  as much as 8% - 20% of the population. The risk for the  prevalence of chronic HB is much more higher among  infants infected during birth 90%, among children of  1 – 5 years  30%  - 60%, and  among adults  2%-6%.  If  infants of  0-7 days old are given  the  first dosage of HB  immunization,  the prevalence of being HB chronic patients  is 23% and  if the  first dosage is given when  infants are one months old,  the prevalence of being HB chronic patients is 40%. The coverage of HB  immunization  for  infants of  0-7 days  old at Banjarmasin Municipality  in 2006 was only  41%.Objective: The  study  aimed  to  identify  the  relationship  between  knowledge,  attitude,  and  behavior  of mothers in giving HB  immunization  to  infants of 0-7 days old at Banjarmasin Municipality.Method: The  study was  observational  and  used  cross  sectional  design. Subject  of   the  study were  170 mothers  having  infants  of  0-12 months chosen  using consecutive  sampling  technique  at 5  health  centers with different  coverage  of HB  immunization  of  infant  of  0-7  days  old. Data analysis  used chi  square  and  logistic regression. Strength  of  relationship was calculated  using  prevalence  ratio with CI  95%.Result:  The  result  of  bivariable  analysis  showed  that  there was  relationship  between  behavior  of mothers  in giving 0-7 day HB  in  immunization and knowledge RP=1.61  (CI 95%=1.35-191), attitude RP=1.49  (CI95%= 1.22-1.62),  education RP=1.56  (CI95%=1.24-1.96),  occupation RP=1.44  (CI95%=1.01-2.05)  and  birth  assistants RP=1.48  (CI95%=1.21-1.82). The  result  of multivariable analysis  using  logistic  regression showed  that only  2 variables,  i.e.  knowledge  and  education  statistically  had  significant  relationship with  behavior  of mothers  in giving 0-7 day HB  immunization.Conclusion: There was  relationship  between  knowledge  and  education  and  behavior  of mothers  in giving  0-7 day HB  immunization.Keywords:  knowledge, attitude,  behavior,  hepatitis B